Ashton Court
Early Renaissance detail has a certain distinction about it, which most certainly results from the lack of understanding local craftsmen had of the new forms. Few English gentlemen and none of the craftsmen had been to Italy and absorbed the Renaissance tradition, by then established for over a century. Consequently, the English craftsman was no longer in command of the product, and from this time on, was required to work from drawings or descriptions. Such restrictions heralded the death of Gothic.